Kawasan Lindung di Kelurahan Balaroa: Dinamika Pembangunan Kembali dan Upaya Pemerintah dalam Pengelolaan Lingkungan - Eisenring, D. Dikwardi; Rusli, Rusli; Fransisko, A. (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2024)
Protected areas play an important role in maintaining environmental sustainability, especially in rapidly developing urban areas. However, managing these protected areas faces significant challenges due to the pressure of space demands for housing and other community activities. This study examines the phenomenon of redevelopment within protected areas in Kelurahan Balaroa, Kota Palu, revealing that disaster-affected communities have chosen to rebuild their homes in these areas. Observations using Geographic Information System (GIS) methods show that approximately 3% of the total protected area is now occupied by buildings, covering around 1.57 hectares. The findings of this study identify the factors motivating the community to rebuild in these areas and explore the government’s efforts to address this issue. A comprehensive understanding of these factors is expected to form the basis for developing more effective policies for sustainable management of protected areas in the future.